Nonlinearity and memory effects in low temperature heat propagation (Archives of Mechanics - Test, 2000)
In order to account for low temperature heat propagation phenomena in crystals of sodium fluoride and bismuth, we employ a thermodynamic model for rigid materials involving a vector-field internal state variable. The model is either wavelike or diffusive, depending on the temperature regime considered.